Description of a new species of Spongiopsyllus Johnsson, 2000, and redescriptions of Parmulodes verrucosus Wilson, 1944 and Entomopsyllus stocki Kim, 2004 with revised diagnosis of Entomopsyllus (Copepoda, Siphonostomatoida, Entomolepididae) - Canário, Roberta; Hurbath, Thiego; Da Rocha, Carlos E. F.; Neves, Elizabeth G.; Johnsson, Rodrigo (Zootaxa, 2019)
The Family Entomolepididae is composed by 7 genera and 15 species. During a survey on the known species and the search for new species, a new Spongiopsyllus is described associated with sponge Aplysina insularis. The new species has antennule 14-segmented, four setae on both lobes of maxillule, some unique features on the leg setation and the armature of the maxilliped. These characteristics make the new species different from all other congeners in Spongiopsyllus. The diagnosis of Entomopsyllus was also revised once it does not consider the differences to Spongiopsyllus which was created posteriorly to its erection. An analysis of Entomopsyllus stocki also indicated that leg 5 somite and the genital somite are fused, instead of separated as originally stated, the structure is also redescribed. Finally, Parmulodes verrucosus is studied and an up-to-date description is provided, correcting some inconsistencies in the armature formula of the antennule and the leg setation, and providing re-analysis of the other appendages.